Transparent electrode film, method for manufacturing the same, and device comprising the same

By forming an electrode layer with a thickness of 200 nm to 1,000 nm on a transparent substrate, and using specific constituent materials and manufacturing methods, the problem of conventional electrode films prone to cracks and increased surface resistance under external stress is solved, and a higher adhesion force and lower crack density and surface resistance increase rate is achieved, which is suitable for equipment such as flexible displays.

CN119731749APending Publication Date: 2025-03-28DONGWOO FINE CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380059286.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-17
Filing Date
2023-07-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Traditional electrode films are prone to cracks and excessive surface resistance under external stress, making them difficult to be suitable for equipment such as flexible displays.

Method used

The thickness of the electrode layer between the transparent substrate and the electrode layer is 200 nm to 1,000 nm. By specific constituent materials and manufacturing methods, it is ensured that at a tensile strain rate of 1% to 10%, the crack density value is between 0 and 0.2 and the plane resistance increase rate is below 15%.

Benefits of technology

It effectively reduces the crack generation and surface resistance increase rate caused by external stress, improves the bonding force between the electrode layer and the substrate, and optimizes the peeling force of the protective film, and is suitable for equipment such as flexible displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731749A_ABST
    Figure CN119731749A_ABST
Patent Text Reader

Abstract

The present invention relates to a transparent electrode film, a method for manufacturing the same, and an apparatus comprising the same, the transparent electrode film comprising a transparent substrate and electrode layers disposed on both surfaces of the transparent substrate, the electrode layers having a thickness of 200 nm to 1,000 nm, and the electrode layers having a crack density value of 0 to 0.2 calculated according to Equation 1 at a tensile strain rate of 1% to 10%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a transparent electrode film, a method for manufacturing the same and a device comprising the same. Background Art

[0002] As computers using digital technology have developed, computer auxiliary devices have also been developed. In particular, personal computers, portable transmission devices, and other personal information processing devices use various input devices (input devices) such as keyboards and mice to process text and graphics.

[0003] However, as the information society develops rapidly, the use of computers is also gradually expanding, and there is a problem that it is difficult to effectively drive products with only the keyboard and mouse that currently serve as input devices. Therefore, there is an increasing demand for devices that are not only simple and less prone to errors, but also allow anyone to easily input information.

[0004] In addition, technologies related to input devices are shifting from the level of satisfying general functions to high reliability, durability, innovation, design and processing related technologies, and in order to achieve these goals, touch panels have been developed as input devices that can input information such as text and graphics.

[0005] Such a touch panel is provided in various display panels as a tool for a user to select desired information while viewing an image display device.

[0006] On the other hand, the types of touch panels are divided into resistive type, capacitive type, electromagnetic type, surface acoustic wave type (SAW type; surface acoustic wave type) and infrared type. These various types of touch panels are adopted in electronic products by considering signal amplification issues, resolution differences, difficulty of design and processing technology, optical properties, electrical properties, mechanical properties, environmental resistance, input characteristics, durability and economy. At present, the most widely used are resistive film type and capacitive type touch panels.

[0007] Such resistive film type and capacitive type touch panels use an electrode layer that generates an electric signal when a user touches the panel. The electrode layer is usually formed in the form of a conductive laminate or an electrode film.

[0008] Korean Patent Publication No. 10-2020-0074862 also discloses an electrode film that can be used for a touch panel, etc.

[0009] On the other hand, in recent years, with the advancement of technology, devices such as flexible displays that use flexible materials as substrates are emerging.

[0010] However, conventional electrode films including the above-mentioned Korean Patent Publication No. 10-2020-0074862 have problems in that the electrode layer may crack due to external stress or the surface resistance may increase excessively, making it unsuitable for use in devices such as flexible displays.

[0011] Therefore, there is an increasing demand for an electrode film that is suitable for use in devices such as flexible displays, without causing cracks in the electrode layer due to external stress and without excessively increasing the surface resistance. Summary of the invention

[0012] Technical issues

[0013] An object of the present invention is to provide a transparent electrode film in which the generation of cracks due to external stress and the rate of increase in sheet resistance are reduced.

[0014] Another object of the present invention is to provide a transparent electrode film having improved adhesion between a transparent substrate and an electrode layer.

[0015] Another object of the present invention is to provide a transparent electrode film having an optimized peeling force of a protective film with respect to an electrode layer.

[0016] Another object of the present invention is to provide a method for producing the transparent electrode film and a device including the transparent electrode film.

[0017] However, the problems to be solved by the present invention are not limited to the problems mentioned above, and a person skilled in the art should be able to clearly understand other problems not mentioned based on the following description.

[0018] Solution to the problem

[0019] The present invention relates to a transparent electrode film, which comprises a transparent substrate and electrode layers arranged on both sides of the transparent substrate, wherein the thickness of the electrode layer is 200nm to 1,000nm, and the crack density value of the electrode layer calculated according to the following formula 1 at a tensile strain rate of 1% to 10% is 0 to 0.2.

[0020] [Formula 1]

[0021]

[0022] (In the above formula 1, the above ε refers to the tensile strain rate (%), and the above A refers to the area of ​​the observation area (mm 2), the above ρ(ε) refers to the crack density value of the electrode layer calculated under the tensile strain rate ε, the above It refers to the crack area of ​​the electrode layer in the observation area A measured at the tensile strain rate ε (mm 2 ). )

[0023] In a first aspect of the present invention, the crack density of the electrode layer calculated according to the above formula 1 at a tensile strain rate of 2% may be 0 to 0.1.

[0024] In a second aspect of the present invention, the crack density of the electrode layer calculated according to the above formula 1 at a tensile strain rate of 2% may be 0.

[0025] In a third aspect of the present invention, the surface resistance increase rate of the electrode layer calculated by the following formula 2 at a tensile strain rate of 1% to 10% may be 15% or less.

[0026] [Formula 2]

[0027] δ(ε)=[{RS(ε) / RS(0)}-1]*100

[0028] (In the above formula 2, the above δ(ε) is the surface resistance increase rate (%) of the electrode layer calculated under the tensile strain rate ε, the above RS(ε) is the surface resistance value (Ω / □) of the electrode layer measured under the tensile strain rate ε, the above RS(0) is the surface resistance value (Ω / □) of the electrode layer measured in the initial state with a tensile strain rate of 0%, and the above ε has the same meaning as in formula 1.)

[0029] In a fourth aspect of the present invention, the surface resistance increase rate of the electrode layer calculated according to the above formula 2 at a tensile strain rate of 1% may be 15% or less.

[0030] In a fifth aspect of the present invention, the surface indentation hardness of the electrode layer can be 150 N / mm 2 Up to 160N / mm 2 .

[0031] In a sixth aspect of the present invention, the surface resistance of the electrode layer may be 400 Ω / □ to 550 Ω / □.

[0032] In a seventh aspect of the present invention, the difference in surface resistance of the electrode layer before and after the light resistance evaluation may be 100 Ω / □ or less.

[0033] In an eighth aspect of the present invention, the electrode layer may be produced from an electrode layer-forming composition containing a conductive polymer and at least one selected from the group consisting of an organic binder, an organic solvent, a silane coupling agent, and a surfactant.

[0034] In a ninth aspect of the present invention, the conductive polymer may include a material selected from the group consisting of polythiophene, poly(3,4-ethylenedioxythiophene), polyaniline, polyacetylene, polydiacetylene, polyphenylene, polyphenylene vinylene, polyphenylene sulfide, polythienylenevinylene, polythiophene One or more of the group consisting of polyvinylene, polyfluorene, polypyrrole, poly(3,4-ethylenedioxythiophene):polystyrenesulfonate, poly(3,4-ethylenedioxythiophene):camphorsulfonic acid, poly(3,4-ethylenedioxythiophene):toluenesulfonate, poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonate, polyaniline:polystyrenesulfonate, polyaniline:camphorsulfonic acid, polypyrrole:polystyrenesulfonate, polypyrrole:camphorsulfonic acid, polypyrrole:toluenesulfonic acid, polypyrrole:dodecylbenzenesulfonic acid, polythiophene:polystyrenesulfonate, polythiophene:camphorsulfonic acid, polythiophene:toluenesulfonic acid and polythiophene:dodecylbenzenesulfonic acid.

[0035] In a tenth aspect of the present invention, the content of the silane coupling agent may be 0.05 wt % to 0.3 wt % based on the total weight of the electrode layer forming composition.

[0036] In an eleventh aspect of the present invention, the transparent substrate may include one or more selected from the group consisting of cycloolefin resins, cellulose resins, acrylic resins, and polyester resins.

[0037] In a twelfth aspect of the present invention, the transparent substrate may have a thickness of 50 μm to 150 μm.

[0038] In a thirteenth aspect of the present invention, a protective film may be provided on one surface of the electrode layer.

[0039] In a fourteenth aspect of the present invention, the peeling force of the protective film may be 1.0 N / 25 mm to 5.0 N / 25 mm.

[0040] In a fifteenth aspect of the present invention, the transparent electrode film may curl to 30 mm or less after the heat resistance evaluation.

[0041] In a sixteenth aspect of the present invention, the transmittance of the transparent electrode film may be 85% or more.

[0042] In the seventeenth aspect of the present invention, the haze of the transparent electrode film may be 1% or less.

[0043] In addition, the present invention relates to a method for manufacturing the above-mentioned transparent electrode film, which includes: a step of providing a transparent substrate (S1); a step of forming a first electrode layer on one side of the above-mentioned transparent substrate (S2); a step of forming a first protective film on one side of the above-mentioned first electrode layer (S3); a step of forming a second electrode layer on the other side of the above-mentioned transparent substrate (S4); and a step of forming a second protective film on one side of the above-mentioned second electrode layer (S5).

[0044] In addition, the present invention relates to a method for manufacturing the above-mentioned transparent electrode film, which includes: a step of providing a transparent substrate (M1); a step of forming a first electrode layer and a second electrode layer on both sides of the above-mentioned transparent substrate (M2); and a step of forming a first protective film and a second protective film on one side of the above-mentioned first electrode layer and the second electrode layer (M3).

[0045] Furthermore, the present invention relates to a device including the above-mentioned transparent electrode film.

[0046] Effects of the Invention

[0047] According to the transparent electrode film of the present invention, the generation of cracks and the rate of increase in surface resistance due to external stress can be further reduced compared with conventional transparent electrode films.

[0048] Furthermore, according to the transparent electrode film of the present invention, the adhesion between the transparent substrate and the electrode layer can be further improved compared to conventional transparent electrode films.

[0049] Furthermore, according to the transparent electrode film of the present invention, the peeling force of the protective film with respect to the electrode layer can be further improved compared with the conventional transparent electrode film. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 and Figure 2 1 is a diagram showing a stacked structure of a transparent electrode film according to one or more embodiments of the present invention.

[0051] Figure 3 This is a diagram showing a method for measuring a crack area of ​​an electrode layer according to an example of the present invention.

[0052] Figure 4 and Figure 5 1 is a diagram showing a method for manufacturing a transparent electrode film according to one or more embodiments of the present invention. DETAILED DESCRIPTION

[0053] The present invention relates to a transparent electrode film in which the generation of cracks and the rate of increase in surface resistance due to external stress are reduced.

[0054] More specifically, the present invention relates to a transparent electrode film comprising a transparent substrate and electrode layers disposed on both sides of the transparent substrate, wherein the thickness of the electrode layer is 200 nm to 1,000 nm, and the crack density value of the electrode layer calculated according to the following formula 1 at a tensile strain rate of 1% to 10% is 0 to 0.2.

[0055] [Formula 1]

[0056]

[0057] (In the above formula 1, the above ε refers to the tensile strain rate (%), and the above A refers to the area of ​​the observation area (mm 2 ), the above ρ(ε) refers to the crack density value of the electrode layer calculated under the tensile strain rate ε, the above It refers to the crack area of ​​the electrode layer in the observation area A measured at the tensile strain rate ε (mm 2 ). )

[0058] In addition, the present invention relates to a method for manufacturing the above-mentioned transparent electrode film, which includes: a step of providing a transparent substrate (S1); a step of forming a first electrode layer on one side of the above-mentioned transparent substrate (S2); a step of forming a first protective film on one side of the above-mentioned first electrode layer (S3); a step of forming a second electrode layer on the other side of the above-mentioned transparent substrate (S4); and a step of forming a second protective film on one side of the above-mentioned second electrode layer (S5).

[0059] In addition, the present invention relates to a method for manufacturing the above-mentioned transparent electrode film, which includes: a step of providing a transparent substrate (M1); a step of forming a first electrode layer and a second electrode layer on both sides of the above-mentioned transparent substrate (M2); and a step of forming a first protective film and a second protective film on one side of the above-mentioned first electrode layer and the second electrode layer (M3).

[0060] Hereinafter, the embodiments of the present invention will be described in more detail with reference to the accompanying drawings. However, the following drawings attached to this specification illustrate preferred embodiments of the present invention, and serve to further understand the above-mentioned invention contents together with the technical ideas of the present invention, so the present invention should not be interpreted only in accordance with the matters recorded in these drawings.

[0061] The terms used in this specification are intended to illustrate the embodiments and are not intended to limit the present invention. In this specification, unless otherwise specified in the context, the singular form also includes the plural form. For example, the "electrode layer" used in this specification may refer to at least one of the first electrode layer and the second electrode layer, and the "protective film" may refer to at least one of the first protective film and the second protective film.

[0062] The terms "comprises" and / or "comprising" used in this specification are used to mean that they do not exclude the existence or addition of one or more other constituent elements, steps, operations and / or elements other than the mentioned constituent elements, steps, operations and / or elements. Throughout the specification, the same reference numerals refer to the same constituent elements.

[0063] As illustrated in the accompanying drawings, spatially relative terms "below", "bottom", "lower", "above", "upper surface", "upper part", etc. can be used to easily describe the correlation between one element or constituent element and other elements or constituent elements. Spatially relative terms should be understood as terms that include different directions of the elements when in use or in operation in addition to the directions illustrated in the drawings. For example, when the elements illustrated in the drawings are turned over, the elements described as "below" or "lower" of other elements can be placed "above" other elements. Therefore, the exemplary term "below" can include both directions below and above. Elements can also be oriented in other directions, so spatially relative terms can be interpreted according to orientation.

[0064] The term “substantially” as used in this specification may be interpreted not only as physically identical or identical but also as including the situation within the error range in the measurement or manufacturing process. For example, it may be interpreted as being within the error range of 0.1% or less.

[0065] Figure 1 and Figure 2 1 is a diagram showing a stacked structure of a transparent electrode film according to one or more embodiments of the present invention.

[0066] Reference Figure 1 and 2 The transparent electrode film of one or more embodiments of the present invention may include a transparent substrate 10 and electrode layers 21, 22 arranged on both sides of the transparent substrate, and may further include protective films 31, 32 arranged on one side of the electrode layers 21, 22 as needed.

[0067] The transparent substrate 10 may be used to provide a structural basis for forming the electrode layers 21 , 22 and the protective films 31 , 32 .

[0068] In one embodiment, in order to improve the transmittance of the transparent electrode film, the transparent substrate 10 preferably has a transmittance of 85% or more, and more preferably has a transmittance of 90% or more.

[0069] The transparent substrate 10 is used as a structural basis for forming the electrode layers 21, 22 and the protective films 31, 32. As long as the transmittance satisfies the above range, there is no particular limitation, and preferably, it may include one or more selected from the group consisting of cycloolefin resin, cellulose resin, acrylate resin, and polyester resin. More specifically, the transparent substrate 10 may be, for example, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), polymethyl methacrylate (PMMA), etc.

[0070] In one embodiment, the transparent substrate 10 may have a thickness of 50 μm to 150 μm. When the thickness of the transparent substrate 10 is less than 50 μm, the electrode layers 21 and 22 and the protective films 31 and 32 may not be well supported. When the thickness is greater than 150 μm, the thickness of the entire film increases due to the excessive thickness, so the transmittance or flexibility of the transparent electrode film may be reduced.

[0071] In one embodiment, in order to improve the adhesion between the electrode layers 21, 22 and the transparent substrate 10, a surface treatment may be applied to one or both surfaces of the transparent substrate 10. The surface treatment is not particularly limited as long as it is used to improve the adhesion between the electrode layers 21, 22 and the transparent substrate 10. For example, a pretreatment process such as corona treatment, plasma treatment, ultraviolet irradiation or primer treatment may be used. When the surface treatment is applied to one or both surfaces of the transparent substrate 10, the adhesion between the electrode layers 21, 22 and the transparent substrate 10 is further improved, and the electrode layers 21, 22 are easily formed on the transparent substrate 10 even if an optically clear adhesive (OCA) film is not included separately, thereby having advantages in terms of improving transmittance and the like.

[0072] The transmittance of the electrode layers 21 and 22 relative to visible light may be 50% or more, and may preferably contain a conductive polymer. The electrode layers 21 and 22 may be made of, for example, a composition for forming an electrode layer comprising a conductive polymer and one or more selected from the group consisting of an organic binder, an organic solvent, a silane coupling agent, and a surfactant, and may further contain a surplus of water according to the needs of the user. In this case, even if the electrode layers 21 and 22 are strained by external stress, cracks can be prevented from being generated, thereby preventing the surface resistance from increasing excessively.

[0073] The conductive polymer may be a conductive polymer material developed in the past or in the future, and may include, for example, a conductive polymer selected from the group consisting of polythiophene, poly(3,4-ethylenedioxythiophene), polyaniline, polyacetylene, polydiacetylene, polyphenylene, polyphenylene vinylene, polyphenylene sulfide, polythiophene acetylene, polythiophene vinylene, polyfluorene, polypyrrole, poly(3,4-ethylenedioxythiophene):polystyrene sulfonate, poly(3,4-ethylenedioxythiophene):camphor sulfonic acid, poly(3,4-ethylenedioxythiophene):toluene sulfonic acid, poly(3,4- At least one of the group consisting of poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid, polyaniline:polystyrenesulfonate, polyaniline:camphorsulfonic acid, polypyrrole:polystyrenesulfonate, polypyrrole:camphorsulfonic acid, polypyrrole:toluenesulfonic acid, polypyrrole:dodecylbenzenesulfonic acid, polythiophene:polystyrenesulfonate, polythiophene:camphorsulfonic acid, polythiophene:toluenesulfonic acid and polythiophene:dodecylbenzenesulfonic acid, preferably poly(3,4-ethylenedioxythiophene) or poly(3,4-ethylenedioxythiophene):polystyrenesulfonate.

[0074] The content of the conductive polymer is not particularly limited, and may be 10 to 65 wt %, preferably 10 to 50 wt %, and more preferably 11 to 30 wt %, relative to the total weight of the electrode layer forming composition.

[0075] The organic binder may include at least one selected from the group consisting of melamine resin, polyester resin, polyurethane resin and polyacrylic resin. In addition, the organic binder may be a water-dispersible resin.

[0076] In one embodiment, the weight average molecular weight of the organic binder may be 5,000 g / mol to 30,000 g / mol, and preferably 10,000 g / mol to 20,000 g / mol.

[0077] The content of the organic binder is not particularly limited, and may be 1 to 20 wt %, preferably 1 to 10 wt %, and more preferably 1 to 5 wt %, relative to the total weight of the electrode layer forming composition.

[0078] The organic solvent may include an alcohol organic solvent, an ether organic solvent and / or an amide organic solvent.

[0079] The alcoholic organic solvent reduces the surface tension of the electrode layer forming composition to improve coating properties. In one embodiment, the alcoholic organic solvent may be an alcohol having 1 to 4 carbon atoms, such as methanol, ethanol, propanol, isopropanol, n-butanol, etc.

[0080] The above-mentioned ether organic solvent can use ether organic solvents developed in the past or in the future, for example, propylene glycol monopropyl ether, propylene glycol monomethyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol-2-ethylhexyl ether, etc. can be used.

[0081] The amide organic solvent serves to improve the conductivity of the electrode layer. In one embodiment, the amide organic solvent may be acetamide, N-methylacetamide, N-dimethylacetamide, N-methylpyrrolidone, etc.

[0082] The content of the organic solvent is not particularly limited, and may be 10 to 80 wt %, preferably 40 to 65 wt %, and more preferably 45 to 60 wt %, relative to the total weight of the electrode layer forming composition.

[0083] The silane coupling agent plays a role in improving the adhesion of the electrode layer-forming composition to facilitate lamination of the electrode layers 21 and 22 on the transparent substrate 10 . In one embodiment, the silane coupling agent may include one or more selected from the group consisting of trimethoxy silane, triethoxy silane, tetramethoxy silane and tetraethoxy silane. For example, the triethoxy silane may be 2-(3,4-epoxycyclohexyl)ethyltriethoxy silane, (3-aminopropyl)triethoxy silane, (pentafluorophenyl)triethoxy silane, (3-glycidyloxypropyl)triethoxy silane or (4-chlorophenyl)triethoxy silane. The trimethoxy silane may be (3-glycidyloxypropyl)trimethoxy silane. trimethoxy silane), (3-chloropropyl)trimethoxy silane, (3-mercaptopropyl)trimethoxysilane, (3-glycidyloxypropyl)trimethoxysilane, (3-aminopropyl)trimethoxy silane, [3-(2-aminoethylamino)propyl]trimethoxy silane, (N,N-dimethylaminopropyl)trimethoxy silane, (3-bromopropyl)trimethoxy silane or (3-iodopropyl)trimethoxy silane.

[0084] From the viewpoint of improving the adhesion between the transparent substrate 10 and the electrode layers 21 and 22 , the content of the silane coupling agent may be 0.05 wt % to 0.3 wt % based on the total weight of the electrode layer forming composition.

[0085] The surfactant may be a silicone-based surfactant or an acetylene-based surfactant, and the silicone-based surfactant may be a modified silicone-based surfactant.

[0086] For example, commercially available products of the silicone-based surfactant include BYK-378 manufactured by BYK, and commercially available products of the acetylene-based surfactant include Dynol 604 manufactured by Air Products.

[0087] The content of the surfactant is not particularly limited, and may be 0.02 wt % to 0.4 wt %, preferably 0.1 wt % to 0.4 wt %, based on the total weight of the electrode layer forming composition.

[0088] In one embodiment, the electrode layers 21 and 22 may have a thickness of 200 nm to 1,000 nm, preferably 200 nm to 500 nm, and more preferably 200 nm to 300 nm. In this case, the electrode layers 21 and 22 may ensure a predetermined transmittance, and the characteristic change caused by external stress is not large, so that a thin electrode film can be manufactured.

[0089] In one embodiment, the crack density of the electrode layers 21 and 22 calculated according to the following formula 1 at a tensile strain rate of 1% to 10% may be 0 to 0.2, preferably 0 to 0.1, and more preferably 0 to 0.05.

[0090] [Formula 1]

[0091]

[0092] In the above formula 1, ε refers to the tensile strain rate (%), and A refers to the area of ​​the observation region (mm 2 ), the above ρ(ε) refers to the crack density value of the electrode layer calculated under the tensile strain rate ε, the above It refers to the crack area of ​​the electrode layer in the observation area A measured at the tensile strain rate ε (mm 2 ).

[0093] Figure 3 This is a diagram showing a method for measuring a crack area of ​​an electrode layer according to an example of the present invention.

[0094] Specifically, refer to Figure 3, the above A may refer to the area of ​​the observation region 1000 arbitrarily specified by the user in order to calculate the crack density value of the electrode layer based on the tensile strain, and the above It can refer to the area (left) of the black portion in the shadow image (right) after converting the image of the electrode layer in the observation area 1000 taken by an optical microscope (OM) or a scanning electron microscope (SEM) into a shadow image (right) using an image processing program such as ImageJ (developed by NIH / LOCI). Figure 3 30.36% in the survey).

[0095] Therefore, the crack density value calculated according to the above formula 1 can be understood as follows: the closer it is to 0, the less likely the electrode layer will produce cracks, and the closer it is to 1, the more likely cracks will occur on the entire surface of the electrode layer.

[0096] That is, when the crack density value calculated according to the above formula 1 at a tensile strain rate of 1% to 10% of the electrode layers 21 and 22 satisfies the above range, it has the following advantages: it can prevent the generation of cracks caused by external stress changes, so stable driving can be achieved even when the external stress changes.

[0097] In another embodiment, the surface resistance increase rate of the electrode layers 21 and 22 calculated according to the following formula 2 at a tensile strain rate of 1% to 10% may be less than 15%, preferably 0% to 14%.

[0098] [Formula 2]

[0099] δ(ε)=[{RS(ε) / RS(0)}-1]*100

[0100] In the above formula 2, the above δ(ε) is the surface resistance increase rate (%) of the electrode layer calculated under the tensile strain rate ε, the above RS(ε) is the surface resistance value (Ω / □) of the electrode layer measured under the tensile strain rate ε, the above RS(0) is the surface resistance value (Ω / □) of the electrode layer measured under the initial state of the tensile strain rate of 0%, and the above ε has the same meaning as in formula 1.

[0101] When the surface resistance increase rate calculated according to the above-mentioned formula 2 under the tensile strain rate of the above-mentioned electrode layers 21 and 22 at 1% to 10% satisfies the above-mentioned range, it has the following advantages: it can prevent the surface resistance from excessively increasing due to changes in external stress, and thus stable driving can be achieved even when the external stress changes.

[0102] On the other hand, from the perspective of smooth driving of the transparent electrode film, the surface resistance value (RS(0)) of the electrode layers 21 and 22 measured in the initial state with the above-mentioned tensile strain rate of 0% can be 400Ω / □ to 550Ω / □, preferably 450Ω / □ to 530Ω / □.

[0103] The surface indentation hardness of the electrode layers 21 and 22 can be 150 N / mm 2 Up to 160N / mm 2 . In this case, the following advantages can be achieved: since the surface hardness is increased compared to the substrate, it is not only easy to protect the electrode film from external impact, but also has appropriate bending characteristics. In one embodiment, the above-mentioned surface indentation hardness evaluation can be measured by a method commonly used in the art. For example, a nanoindentation device can be used to measure the surface indentation hardness during the maximum load arrival time of 10 seconds to 20 seconds with a load of 0.05 mN to 0.3 mN.

[0104] The surface resistance difference of the electrode layers 21 and 22 before and after the light resistance evaluation may be 100Ω / □ or less. In this case, the sensitivity of the touch sensor may not be reduced by external light and may remain the same. In one embodiment, the light resistance evaluation may be measured by a method commonly used in the art, for example, by using a fade meter.

[0105] The protective films 31 and 32 may be provided to prevent scratches, contamination, corrosion, etc. on the surface of the electrode layers 21 and 22 that may occur during the manufacture, transportation or storage of the transparent electrode film, and may be peeled off and removed from the transparent electrode film before the transparent electrode film is used in the device.

[0106] The peeling force of the protective films 31 and 32 relative to the transparent electrode film, more specifically relative to the electrode layers 21 and 22, is preferably 1.0N / 25mm to 5.0N / 25mm. The peeling force can be measured by a universal testing machine at a speed of 30mm / min at a 90° peeling force (N / 25mm) between the electrode layers 21 and 22 and the protective films 31 and 32. When the peeling force of the protective films 31 and 32 meets the above range, bubbles will not be introduced when manufacturing the transparent electrode film, and the electrode layers 21 and 22 will not be damaged when the protective films 31 and 32 are peeled off from the electrode layers 21 and 22, which can further improve the durability of the electrode film.

[0107] The protective films 31 and 32 may include a base film and an adhesive layer formed on the base film.

[0108] The substrate film may be a substrate film developed in the past or in the future, for example, it may include one or more selected from the group consisting of polyolefin films, polyester films, acrylic films, styrene films, amide films, polyvinyl chloride films, polyvinylidene chloride films and polycarbonate films. Considering the possibility of deformation during the manufacture, transportation or storage of the transparent electrode film, the adhesion to the electrode layers 21 and 22, etc., the thickness of the substrate film may be 200 μm to 300 μm.

[0109] The adhesive layer can be formed using an adhesive, and preferably only the protective films 31 and 32 are cleanly removed from the electrode layers 21 and 22 when peeling off the protective films 31 and 32. It has appropriate adhesion so as not to affect other components such as the electrode layers 21 and 22, and has transparency and thermal stability.

[0110] The adhesive may be an adhesive developed in the past or in the future, and in one or more embodiments, may be an acrylic adhesive, a rubber adhesive, a silicone adhesive, a urethane adhesive, a polyvinyl alcohol adhesive, a polyvinyl pyrrolidone adhesive, a polyacrylamide adhesive, a cellulose adhesive, a vinyl alkyl ether adhesive, etc. The adhesive is not particularly limited as long as it has adhesive force and viscoelasticity, but in terms of ease of acquisition, it is preferably an acrylic adhesive, for example, it may contain a (meth)acrylate copolymer, a crosslinking agent, a solvent, etc.

[0111] The crosslinking agent may be any crosslinking agent developed in the past or in the future, and may include, for example, polyisocyanate compounds, epoxy resins, melamine resins, urea resins, dialdehydes, methylol polymers, and preferably polyisocyanate compounds.

[0112] The above-mentioned solvent may include a common solvent used in the field of resin compositions, for example, alcohol compounds such as methanol, ethanol, isopropanol, butanol, propylene glycol methoxy alcohol, ketone compounds such as methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, dipropyl ketone, acetate compounds such as methyl acetate, ethyl acetate, butyl acetate, propylene glycol methoxy acetate, cellosolve compounds such as methyl cellosolve, ethyl cellosolve, propyl cellosolve, hydrocarbon compounds such as hexane, heptane, benzene, toluene, xylene, etc. Solvents such as these can be used. These solvents can be used alone or in combination of two or more.

[0113] The thickness of the adhesive layer can be appropriately determined according to the type of resin that functions as an adhesive, the adhesive strength, the environment in which the adhesive is used, etc. In one embodiment, the adhesive layer can have a thickness of 1 μm to 30 μm so that the peeling force of the protective films 31 and 32 reaches 1.0 N / 25 mm to 2.4 N / 25 mm.

[0114] The transparent electrode film of the present invention, which is composed of the components satisfying the above technical characteristics, can not only reduce the occurrence of curl, but also have excellent transmittance and reduce haze.

[0115] Specifically, the curl of the transparent electrode film of the present invention after heat resistance evaluation can be less than 30 mm. In one embodiment, the heat resistance evaluation can be performed by placing the transparent electrode film at a temperature of 70°C to 90°C for 10 to 50 minutes and then measuring the curl of the transparent electrode film at room temperature.

[0116] In addition, the transparent electrode film of the present invention may have a transmittance of 85% or more and a haze of 1% or less, thereby further improving the optical characteristics of a device to which the transparent electrode film is applied.

[0117] Figure 4 and Figure 5 1 is a diagram showing a method for manufacturing a transparent electrode film according to one or more embodiments of the present invention.

[0118] Reference Figure 4 A method for manufacturing a transparent electrode film according to an embodiment of the present invention may include: a step of providing a transparent substrate 10 (S1); a step of forming a first electrode layer 21 on one surface of the transparent substrate 10 (S2); a step of forming a first protective film 31 on one surface of the first electrode layer 21 (S3); a step of forming a second electrode layer 22 on the other surface of the transparent substrate 10 (S4); and a step of forming a second protective film 32 on one surface of the second electrode layer 22 (S5).

[0119] Reference Figure 5 A method for manufacturing a transparent electrode film according to another embodiment of the present invention may include: a step of providing a transparent substrate 10 (M1); a step of forming a first electrode layer 21 and a second electrode layer 22 on both sides of the transparent substrate 10 (M2); and a step of forming a first protective film 31 and a second protective film 32 on one side of the first electrode layer 21 and the second electrode layer 22 (M3).

[0120] In one embodiment, the step of forming the electrode layers 21 and 22 can be implemented by printing, for example, gravure printing, screen printing, offset printing, inkjet printing, etc. In this case, a composition for forming an electrode layer containing a conductive polymer (for example, PEDOT:PSS) can be used and used for each printing method with an appropriate viscosity.

[0121] In one embodiment, the step of forming the protective films 31 and 32 may be implemented by lamination, but is not limited thereto.

[0122] In addition to the transparent electrode film and its manufacturing method, the present invention also includes a device having the transparent electrode film. The device is not particularly limited as long as it is a device in the technical field of the transparent electrode film of the present invention, for example, it can be used in a touch panel that can be used in a flexible display.

[0123] Implementation

[0124] The following specifically describes the embodiments of the present invention. However, the present invention is not limited to the embodiments disclosed below, but can be implemented in various different ways. The embodiments are only provided to make the disclosure of the present invention complete and to fully inform the general technicians of the technical field to which the present invention belongs of the scope of the invention. The present invention is only defined by the scope of the claims.

[0125] Examples and Comparative Examples: Preparation of Transparent Electrode Films

[0126] Example 1

[0127] A PEDOT electrode layer forming composition is coated on both sides of a 50 μm thick polyethylene terephthalate (PET) film and dried at 90° C. for about 5 to 10 minutes to form an electrode layer with a thickness of 200 nm, thereby preparing a transparent electrode film of Example 1 having a stacked structure of electrode layer (PEDOT) / transparent substrate (PET) / electrode layer (PEDOT).

[0128] At this time, the composition for forming the PEDOT electrode layer is a mixture of 13 wt % of PEDOT:PSS, 2 wt % of polyester resin, 50 wt % of ethanol, and 35 wt % of water.

[0129] Example 2

[0130] A transparent electrode film of Example 2 having a stacked structure of electrode layer (PEDOT) / transparent substrate (COP) / electrode layer (PEDOT) was prepared by the same manufacturing method as Example 1 except that a 50 μm thick cycloolefin polymer (COP) film was used as the transparent substrate.

[0131] Example 3

[0132] A transparent electrode film of Example 3 having a stacked structure of electrode layer (PEDOT) / transparent substrate (TAC) / electrode layer (PEDOT) was prepared by the same manufacturing method as Example 1 except that a 50 μm thick triacetyl cellulose (TAC) film was used as the transparent substrate.

[0133] Comparative Example 1

[0134] A polyethylene terephthalate (PET) film with a thickness of 50 μm was placed, a 450 W DC power supply was applied to start the sputtering gun, and then plasma was induced to the ITO (10 wt % Sn-doped In2O3) target to form an indium tin oxide (ITO) electrode layer with a thickness of 100 nm on both sides of the PET film, thereby producing a transparent electrode film of Comparative Example 1 having a stacked structure of electrode layer (ITO) / transparent substrate (PET) / electrode layer (ITO).

[0135] Comparative Example 2

[0136] A transparent electrode film of Comparative Example 2 having a stacked structure of electrode layer (AgNW) / transparent substrate (PET) / electrode layer (AgNW) was prepared by the same manufacturing method as Comparative Example 1 except that silver nanowires (AgNW) with a thickness of 100 nm were used as the electrode layer.

[0137] Comparative Example 3

[0138] A transparent electrode film of Comparative Example 3 having a laminated structure of electrode layer (Cu metal mesh) / transparent substrate (PET) / electrode layer (Cu metal mesh) was prepared by the same manufacturing method as Comparative Example 1, except that a copper mesh electrode with a thickness of 100 nm was used as the electrode layer.

[0139] Experimental example

[0140] (1) Crack density and surface resistance evaluation

[0141] For the transparent electrode films of the above embodiments and comparative examples, the crack density and the surface resistance increase rate were calculated according to Formulas 1 and 2 for the tensile strain rates of 0%, 1%, 2% and 10% in the transverse direction (TD), respectively. The results are shown in Tables 1 and 2 below.

[0142] It should be noted that the crack density and the sheet resistance increase rate described in Tables 1 and 2 are larger values ​​among the measured values ​​of the first electrode layer and the second electrode layer.

[0143] (2) Transmittance and haze evaluation

[0144] The transparent electrode film samples of the examples and comparative examples were cut into pieces of 150 mm x 100 mm, and the transmittance and haze were measured using a haze meter (HM-150). The results are shown in Tables 1 and 2 below.

[0145] (3) Surface indentation hardness evaluation

[0146] The transparent electrode films of the examples and comparative examples were cut into pieces of 50 mm x 50 mm, and the surface indentation hardness of the electrode layer was measured using a nanoindenter (FISHER HM500) at a load of 0.1 mN until the maximum load reached 15 seconds. The results are shown in Tables 1 and 2 below.

[0147] It should be noted that the surface indentation hardness values ​​described in Tables 1 and 2 are averages of the measured values ​​of the first electrode layer and the second electrode layer.

[0148] (4) Light resistance evaluation

[0149] The electrode layers of the transparent electrode films of the examples and comparative examples were evaluated for light resistance using a discoloration meter by irradiating light under the following conditions, and then the surface resistance difference before and after the evaluation was calculated. The results are shown in Tables 1 and 2 below.

[0150] The light irradiation conditions in the light resistance test are as follows.

[0151] Equipment used: U48AU (SUGA)

[0152] Light source: Carbon Arc lamp

[0153] Exposure conditions: 500W / m 2

[0154] Test time: 120 hours

[0155] Exposure: 216000kJ / m 2

[0156] Temperature: 60℃

[0157] It should be noted that the sheet resistance difference described in Tables 1 and 2 is the larger value of the measured values ​​of the first electrode layer and the second electrode layer.

[0158] (5) Heat resistance evaluation

[0159] The transparent electrode film samples of the examples and comparative examples were cut into 300 mm x 200 mm pieces, placed in a heat-resistant oven at 80°C for 30 minutes, and then measured for curl at room temperature. After the heat resistance evaluation, the curl of the transparent electrode film was measured, and the results are shown in Tables 1 and 2 below.

[0160] [Table 1]

[0161]

[0162] [Table 2]

[0163]

[0164]

[0165] Referring to Tables 1 and 2 above, it can be seen that the transparent electrode films of Examples 1 to 3 have crack density values ​​of 0 and surface resistance increase rates of 15% or less measured at tensile strain rates of 1% to 10%. In addition, it can be seen that not only the transmittance, haze and heat resistance evaluation results are good, but also the surface resistance increase value in the light resistance evaluation is a maximum of +52Ω / □ and the surface indentation hardness is good, showing excellent characteristics.

[0166] On the other hand, it can be seen that the crack density value of the transparent electrode film of Comparative Examples 1 to 3 measured at a tensile strain rate of 1% to 10% is a maximum of 0.72, and the surface resistance increase rate is a maximum of 4,262,421%, which is significantly higher than that of the embodiment. In addition, it can be seen that the surface resistance increase value in the light resistance evaluation is a maximum of +466Ω / □, which is significantly higher than that of the embodiment.

[0167] From these results, it can be seen that the transparent electrode film of the present invention not only has a small change in crack density and surface resistance due to tensile strain, but also has excellent optical properties such as transmittance and haze, and further has excellent light resistance and heat resistance.

[0168] Industrial Applicability

[0169] According to the transparent electrode film of the present invention, the generation of cracks and the rate of increase in surface resistance due to external stress can be further reduced compared with conventional transparent electrode films.

Claims

1. A transparent electrode film comprising a transparent substrate and electrode layers disposed on both sides of the transparent substrate, The thickness of the electrode layer is 200 nm to 1,000 nm, The crack density of the electrode layer calculated according to the following formula 1 at a tensile strain rate of 1% to 10% is 0 to 0.2, [Formula 1] ρ(ε)=l(ε) / A In the formula 1, ε refers to the tensile strain rate, A refers to the area of ​​the observation region, ρ(ε) refers to the crack density value of the electrode layer calculated under the tensile strain rate ε, and l(ε) refers to the crack area of ​​the electrode layer in the observation region A measured under the tensile strain rate ε, wherein, The unit of tensile strain rate is %, and the unit of the area of ​​the observation area and the crack area of ​​the electrode layer is mm 2 . 2 . The transparent electrode film according to claim 1 , wherein the crack density of the electrode layer calculated according to Formula 1 at a tensile strain rate of 2% is 0 to 0.

1. 3 . The transparent electrode film according to claim 2 , wherein the crack density of the electrode layer calculated according to Formula 1 at a tensile strain rate of 2% is 0.

4. The transparent electrode film according to claim 1, wherein the surface resistance increase rate of the electrode layer calculated according to the following formula 2 at a tensile strain rate of 1% to 10% is 15% or less, [Formula 2] δ(ε)=[{RS(ε) / RS(0)}-1]*100 In Formula 2, δ(ε) is the surface resistance increase rate of the electrode layer calculated at the tensile strain rate ε, RS(ε) is the surface resistance value of the electrode layer measured at the tensile strain rate ε, RS(0) is the surface resistance value of the electrode layer measured in the initial state with a tensile strain rate of 0%, and ε has the same meaning as in Formula 1, wherein, The unit of the increase rate of the surface resistance of the electrode layer is %, and the unit of the surface resistance value of the electrode layer is Ω / □. 5 . The transparent electrode film according to claim 4 , wherein the surface resistance increase rate of the electrode layer calculated according to Formula 2 at a tensile strain rate of 1% is 15% or less.

6. The transparent electrode film according to claim 1, wherein the surface indentation hardness of the electrode layer is 150 N / mm 2 Up to 160N / mm 2 . 7 . The transparent electrode film according to claim 1 , wherein the surface resistance of the electrode layer is 400 Ω / □ to 550 Ω / □. 8 . The transparent electrode film according to claim 1 , wherein a difference in surface resistance of the electrode layer before and after light resistance evaluation is 100 Ω / □ or less. 9 . The transparent electrode film according to claim 1 , wherein the electrode layer is made of an electrode layer-forming composition comprising a conductive polymer and at least one selected from the group consisting of an organic binder, an organic solvent, a silane coupling agent, and a surfactant.

10. The transparent electrode film according to claim 9, wherein the conductive polymer comprises a material selected from the group consisting of polythiophene, poly(3,4-ethylenedioxythiophene), polyaniline, polyacetylene, polydiacetylene, polyphenylene, polyphenylene vinylene, polyphenylene sulfide, polythiophene acetylene, polythiophene vinylene, polyfluorene, polypyrrole, poly(3,4-ethylenedioxythiophene):polystyrene sulfonate, poly(3,4-ethylenedioxythiophene):camphor sulfonic acid, poly(3,4-ethylenedioxythiophene): One or more of the group consisting of poly(3,4-ethylenedioxythiophene):toluenesulfonic acid, poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid, polyaniline:polystyrenesulfonate, polyaniline:camphorsulfonic acid, polypyrrole:polystyrenesulfonate, polypyrrole:camphorsulfonic acid, polypyrrole:toluenesulfonic acid, polypyrrole:dodecylbenzenesulfonic acid, polythiophene:polystyrenesulfonate, polythiophene:camphorsulfonic acid, polythiophene:toluenesulfonic acid and polythiophene:dodecylbenzenesulfonic acid. 11 . The transparent electrode film according to claim 9 , wherein the content of the silane coupling agent is 0.05 wt % to 0.3 wt % based on the total weight of the electrode layer forming composition. 12 . The transparent electrode film according to claim 1 , wherein the transparent substrate comprises at least one selected from the group consisting of cycloolefin resins, cellulose resins, acrylate resins, and polyester resins. 13 . The transparent electrode film according to claim 1 , wherein the transparent substrate has a thickness of 50 μm to 150 μm. 14 . The transparent electrode film according to claim 1 , further comprising a protective film disposed on one side of the electrode layer. 15 . The transparent electrode film according to claim 14 , wherein the peeling force of the protective film is 1.0 N / 25 mm to 5.0 N / 25 mm. 16 . The transparent electrode film according to claim 1 , wherein the transparent electrode film has a curl of 30 mm or less after heat resistance evaluation. 17 . The transparent electrode film according to claim 1 , wherein the transmittance of the transparent electrode film is 85% or more. 18 . The transparent electrode film according to claim 1 , wherein the haze of the transparent electrode film is 1% or less.

19. A method for manufacturing the transparent electrode film according to claim 1, comprising: Step S1 of providing a transparent substrate; Step S2 of forming a first electrode layer on one surface of the transparent substrate; Step S3 of forming a first protective film on one side of the first electrode layer; Step S4 of forming a second electrode layer on the other surface of the transparent substrate; and Step S5 of forming a second protective film on one side of the second electrode layer.

20. A method for manufacturing the transparent electrode film according to claim 1, comprising: A step M1 of providing a transparent substrate; Step M2 of forming a first electrode layer and a second electrode layer on both sides of the transparent substrate respectively; as well as A step M3 of forming a first protective film and a second protective film on one side of the first electrode layer and the second electrode layer, respectively.

21. A device comprising the transparent electrode film according to any one of claims 1 to 18.

Citation Information

Patent Citations

  • Conductive film with protective film and method of manufacturing conductive film

    KR1020200074862A